2015
DOI: 10.1111/ajt.13275
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Extracellular HMGB1 Suppresses Xenoreactive B Cell Responses and Delays Acute Vascular Xenogeneic Rejection

Abstract: Blockade of extracellular high mobility group box 1 (HMGB1) can significantly prolong murine cardiac allograft survival. Here, we determined the role of HMGB1 in xenotransplantation. Sprague‐Dawley rat hearts were transplanted heterotopically into BALB/c mice. Xenografts without any treatment developed predominant acute vascular rejection within 6 days. Both passively released HMGB1 from xenografts and actively secreted HMGB1 from infiltrated immune cells were significantly increased after xenotransplantation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…[1][2][3][4][5] These cytokines play important roles in inflammation in human diseases. Various pro-inflammatory cytokines are also produced and cross-react with donor or recipient cells in xenotransplantation, [6][7][8][9][10][11][12] and we predict that they will play important roles in the immune and coagulation responses. Many pro-inflammatory cytokines increase the expression of tissue factor (TF), which promotes activation of coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] These cytokines play important roles in inflammation in human diseases. Various pro-inflammatory cytokines are also produced and cross-react with donor or recipient cells in xenotransplantation, [6][7][8][9][10][11][12] and we predict that they will play important roles in the immune and coagulation responses. Many pro-inflammatory cytokines increase the expression of tissue factor (TF), which promotes activation of coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…12 Anti-HMGB1 treatment can significantly prolong cardiac xenograft survival in a rat-to-mouse model. 13 However, HMGB1-mediated activation of porcine endothelial cells has not been explored, and the protective effect of hTBM against HMGB1's actions in this setting has not been examined. We therefore aimed to test HMGB1-mediated proinflammatory and procoagulant effects on PAEC and to assess the capacity of transgenic expression of hTBM on PAEC to neutralize HMGB1.…”
mentioning
confidence: 99%
“…Similar to IL-1a, HMGB1 also turns myeloid APCs into potent T cell stimulators by upregulating APC costimulatory molecules and inducing proinflammatory cytokine secretion by APCs, particularly IL-12p70 (20). As expected from these properties, released HMGB1 supports IRI (32,33) and the alloimmune response leading to GVHD (34) and transplant rejection (35)(36)(37)(38). Zou et al delivered anti-HMGB1 antibody to C57BL/6 recipients for 4 weeks after heterotopic transplantation of MHC class II disparate bm12 hearts and demonstrated that HMGB1 release supports chronic cardiac rejection (38).…”
Section: Alarmins As Proinflammatory Mediators After Transplantationmentioning
confidence: 99%
“…Mechanistic studies indicated that decreases in systemic HMGB1 result in less activated DCs and thus reduced Th1 and Th17 responses (38). Li et al established that anti-HMGB1 antibodies suppressed B cell activation and reduced IFN-c and IL-17A production after xenotransplantation of rat hearts into BALB/c mice (36). Anti-HMGB1 antibody delivery promoted allogeneic islet survival (39,40).…”
Section: Alarmins As Proinflammatory Mediators After Transplantationmentioning
confidence: 99%